Employee interests in the light of human resource management concepts = Interesy pracowników w świetle koncepcji zarządzania ludźmi - Gableta, Małgorzata; Bodak, Andrzej (Zielona Góra: Faculty of Economics and Management Press)
Representation of employee interests is addressed, as reflected in the modern human resource management concepts. By attending to the need of respecting employee interests, companies may greatly increase their chances of reaching company business objectives and increase their effectiveness, as a result of improved employee involvement. Direct and indirect expressions of this aspect in modern HRM concepts are discussed.
Keywords: human resources management (HRM); interesy pracownicze; prawa pracownicze; zaangażowanie; employee interests; employee rights; involvement